Cassava toxicity, detoxification and its food applications: a review. (2nd January 2021) - Panghal, Anil; Munezero, Claudia; Sharma, Paras; Chhikara, Navnidhi
Abstract: Cassava ( Manihot esculenta Crantz) is drought resistant staple food in tropical and subtropical regions and containing starch in higher amount. Cassava starch, being cheap and abundantly available, is capable of providing food security of the world. In addition to direct food and feed consumption of cassava, cassava has great potential in industry applications. The high starch content of cassava root accounts for its suitability in wide range of pharmaceutical, textile, detergent, plastic industries, food industries and feed industries. Cassava starch is used as base ingredients in various starch based foods like soups, bakery and in manufacturing of edible plastic food packaging material. However, cyanogenic glycosides secreted in cassava for self-defense produce hydrogen cyanide on hydrolysis and are accounting for its toxicity and safety concerns. Different processing treatment like peeling, washing, drying, fermentation, grating, boiling, and chemical treatments are used for cassava detoxification.